1996
DOI: 10.1016/0014-5793(96)01125-8
|View full text |Cite
|
Sign up to set email alerts
|

NAD+‐dependent internalization of the transmembrane glycoprotein CD38 in human Namalwa B cells

Abstract: CD38 is a transmembrane glycoprotein involved as an orphan receptor in many physiological processes of lymphocytes. It is also a bifunctional enzyme that catalyzes at its ectocellular domain the synthesis from NAD + (cyclase) and the hydrolysis (hydrolase) of the calcium-mobilizing metabolite cyclic ADPribose (cADPR). A still unexplained paradox concerns the relationship between ectocellular localization of CD38 and intracellular calcium-releasing activity of its intermediate product cADPR. Incubation of CD38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 33 publications
5
65
2
1
Order By: Relevance
“…Therefore, expression of CD38 results in intracellular cADPR production. This is also confirmed by the fact that Namalwa cells, which show ectocellular cyclase levels similar to the CD38 ϩ 3T3 cells of this study, also have comparable [cADPR] i (17). The mechanism whereby NAD ϩ gains access to the apparently secluded catalytic domain of CD38 in (exo/ endocytotic) vesicles remains undetermined.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, expression of CD38 results in intracellular cADPR production. This is also confirmed by the fact that Namalwa cells, which show ectocellular cyclase levels similar to the CD38 ϩ 3T3 cells of this study, also have comparable [cADPR] i (17). The mechanism whereby NAD ϩ gains access to the apparently secluded catalytic domain of CD38 in (exo/ endocytotic) vesicles remains undetermined.…”
Section: Discussionsupporting
confidence: 67%
“…Internalization of membrane-bound CD38, as observed in human Namalwa B-lymphocytes upon incubation with NAD ϩ or thiol reagents, is followed by an increase of intracellular cyclase activity (insensitive to protein synthesis inhibitors) and of intracellular cADPR concentration ([cADPR] i ) (17), suggesting that cytosolic NAD ϩ is available to intravesicular CD38. This observation prompted us to investigate whether modulation of the ectocellular expression of CD38 could affect both the [cADPR] i and the free cytosolic ionized calcium concentration ([Ca 2ϩ ] i ).…”
mentioning
confidence: 99%
“…3E). CD38 is known to be activated via its internalization from the plasma membrane through its association with phosphorylated MHCIIA by protein kinase G (23). To verify this notion, we treated J774A.1 macrophages with a specific MHCIIA inhibitor, blebbistatin (62), which completely blocked the IgG-opsonized latex beadinduced Ca 2ϩ signaling (Fig.…”
Section: Igg-opsonized Latex Beads Induce Fc␥r-mediated Phagocytosis mentioning
confidence: 99%
“…It has also been suggested that CD38 is internalized once activated via endocytosis, thus allowing its catalytic site to interact with intracellular substrates (19 -21). This internalizing event has been observed in many different cellular responses where cADPR production is shifted from the surface to inside the cell (22,23). It has been suggested that the internalization mechanism is mediated by non-muscle myosin heavy chain IIA (MHCIIA), where both CD38 and MHCIIA were found to be associated in activated lymphokine-activated killer cells (24).…”
mentioning
confidence: 99%
“…cADPR has also been shown to augment the proliferative response of activated murine B lymphocytes (5), as well as to mediate the Ca 2ϩ release associated with ATP-activated potassium currents in alveolar macrophages (10), suggesting that cADPR may function as a signaling second messenger in multiple hematopoietic cell types. Although the physiological ligand for CD38 has yet to be identified, CD38 was reported to undergo internalization through non-clathrincoated endocytic vesicles upon incubating cells with thiol compounds or NAD (11). The mechanism by which endocytic vesicles can generate cADPR was suggested by the demonstration that the CD38-catalyzed conversion of NAD to cADPR can be achieved by the influx of cytosolic NAD into the endocytic vesicles and the cADPR into the cytosol for subsequent Ca 2ϩ signaling (12).…”
mentioning
confidence: 99%